THE COGNITIVE ASPECT DEVELOPMENT OF MATCHING NUMBERS SYMBOLS IN CHILDREN - Murni, Seroja; Aslamiah; Rachmayani , Ririanti (Indonesian Researcher Society for Science Technology and Education (IDREST) Publisher, 2019)
The learning activity by using the picture and picture, make a matching model uses various goods near the children has an aim to increase the cognitive aspect development of B Group in the Anak Bangsa Marabahan Kindergarten, Marabahan sub-district, Barito Kuala District with 18 students which consist of 6 females and 12 males. The data was collected by observing the teacher, student?s activities, and the development of the study results. The result of this study shows that there are various enhancements in the cognitive aspect development in matching numbers with the number symbol through the combination model of Picture and Picture, Make a Match. The result of the teacher?s activity cycle 1 showed a score of 22, and in cycle IV it got a score of 41. Meanwhile, the students? activity reached up to 50% in cycle 1 and reached 82.63% in cycle IV. The cognitive development result in cycle 1 reached 49.3%, and it reached 91.67% in cycle IV.